Occupational skin problems in construction workers - Shah Kartik; Tiwari Rajnarayan (Wolters Kluwer Medknow Publications, 2010)
Background : Construction workers handle cement which has constituents to produce both irritant contact dermatitis and corrosive effects (from alkaline ingredients, such as lime) and sensitization, leading to allergic contact dermatitis (from ingredients, such as chromium). Aim: The present study has been carried out among unorganized construction workers to find the prevalence of skin problems. Materials and Methods: The present cross-sectional study was conducted in 92 construction workers of Ahmedabad and Vadodara. Results and Discussion: All the workers were subjected to clinical examination after collection of information regarding demographic characteristics, occupational characteristics and clinical history on a predesigned proforma. Of them, 47.8% had morbid skin conditions. Frictional callosities in palm were observed in 18 (19.6%) subjects while 4 (4.3%) subjects had contact dermatitis. Other conditions included dry, fissured and scaly skin, infectious skin lesion, tinea cruris, lesion and ulcers on hands and/or soles. Conclusion : The skin conditions were common in the age group of 20-25 years, males, those having ≥1 year exposure and those working for longer hours. Half of the workers not using personal protective equipment had reported skin-related symptoms.